Situational Analysis on residents of MIMAROPA Youth Center: A Basis for Program Proposal - Piol-Salazar Ciedelle; Tolentino Jerome; Cadao Jobeth (Universidade Estadual de Alagoas, 2024)
This study focused on analyzing the situation and experiences of residents in MIMAROPA Youth Center, Poblacion, Bansud, Oriental Mindoro and the status of programs, services, and facilities. It aimed to understand the significant effects of government interventions to the rehabilitation process of children-in-conflict with the law using a phenomenological design of qualitative research. The respondents of the study were five residents and six informants from MYC staff, selected purposively. This study used photovoice technique, an interview, observation, and document analysis to gather the necessary information. Using the design, it was able to describe the lived experiences of residents in MYC, their situation, and the effects of the programs and services on the rehabilitation of residents. It was discovered that, while programs and services are adequate, there are still gaps in their implementation, resulting in residents' boredom, anxiety, and stress. The study also found out that the programs and services offered by the MYC are beneficial and effective for its residents, as they helped themselves developed as children and prepared them for their reintegration.